1990
DOI: 10.1021/jo00293a014
|View full text |Cite
|
Sign up to set email alerts
|

Tungstate-catalyzed oxidation of tetrahydroquinolines with hydrogen peroxide: A novel method for the synthesis of cyclic hydroxamic acids

Abstract: The sodium tungstate catalyzed oxidation of 1,2,3,4-tetrahydroquinolines (1) with 30% aqueous hydrogen peroxide solution in methanol gives l-hydroxy-3,4-dihydroquinolin-2(lH)-ones (2), which are important biologically active compounds, in good to excellent yields. The cyclic hydroxamic acid 7 is also obtained in good yield. Since reduction of 2 thus obtained gives 3,4-dihydroquinolin-2(lff)-ones (4), the present reaction provides a convenient method for synthesis of 4 from 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…Functionalization of the sp 3 C–H bond α to the nitrogen atom in tetrahydroquinolines and indolines via iminium ions is challenging because the corresponding iminium ions are enolizable and thus tend to tautomerize to enamines [9495] and/or aromatize [9697]. The authors adopted a strategy to bypass the iminium ions and use α-amino radicals such as 112 instead to construct C–N bonds.…”
Section: Reviewmentioning
confidence: 99%
“…Functionalization of the sp 3 C–H bond α to the nitrogen atom in tetrahydroquinolines and indolines via iminium ions is challenging because the corresponding iminium ions are enolizable and thus tend to tautomerize to enamines [9495] and/or aromatize [9697]. The authors adopted a strategy to bypass the iminium ions and use α-amino radicals such as 112 instead to construct C–N bonds.…”
Section: Reviewmentioning
confidence: 99%
“…Oxidation of Amines Catalyzed by PWAA Since PWAA efficiently promoted the epoxidation of allylic alcohols, we applied this oxidation system to secondary amines. [45][46][47][48][49][50][51][52][53][54][55][56] Oxidation of secondary amines is the most straightforward method and the direct route to prepare nitrones, which are important substrates for the synthesis of nitrogen-containing bioactive compounds. It was beforehand confirmed that no oxidation of dibenzylamine (11a) with hydrogen peroxide was observed at room temperature.…”
Section: Epoxidation Of Allylic Alcoholsmentioning
confidence: 99%
“…Similarly, when benzylamine 9a was reacted under our optimised conditions, no hydroisoquinoline was evidenced by 1 H NMR, only partial conversion into its oxidised analogue, isoquinoline 10a (Table , entry 9). While we could not find precedents with copper for this transformation in the literature, we would expect the metal to be involved in this aerobic aromatisation of the intermediate 1,2‐dihydroisoquinoline …”
Section: Resultsmentioning
confidence: 84%